Phylogenetic patterns of rarity in a regional species pool of tropical woody plants. Issue 9 (28th July 2017) - Loza, M. Isabel; Jiménez, Iván; Jørgensen, Peter M.; Arellano, Gabriel; Macía, Manuel J.; Torrez, Vania W.; Ricklefs, Robert E.
Abstract: Aim: Rarity, which is believed to influence extinction risk, can be defined in terms of local abundance, geographical range size and habitat breadth. Phylogenetic patterns in these attributes provide insight into the extent to which rarity and extinction risk are conserved during evolution and the potential for species‐level heritability. We evaluated phylogenetic signal (i.e., related species resembling each other more than species drawn at random) and evolutionary conservatism (similarity among related species exceeding that expected from a Brownian model of evolution) in three axes of rarity (local abundance, geographical range size and habitat breadth) among species in a regional pool of tropical woody plants. Location: The Madidi region in Bolivia. Time period: 2001–2010. Major taxa studied: Lignophyta clade. Methods: We used a network of 48 1‐ha forest plots and 442 0.1‐ha forest plots to measure local abundance and habitat breadth of 1, 700+ woody plant species (from 100+ plant families). We estimated geographical range size from occurrence records of individual species across the Neotropics. We characterized overall phylogenetic patterns of rarity using Blomberg's K and applied variance partitioning among taxonomic levels, as well as disparity analysis, to describe patterns of trait distribution at different depths in the phylogeny. Results: We found phylogenetic signal, but not evolutionary conservatism, in the three axes of rarity. The variance in rarity among supra‐specific taxa, particularly families and genera, exceeded that calculated from random draws of species from the Madidi region. Phylogenetic signal, estimated by the proportion of variance among supra‐specific taxonomic levels, varied between 23 and 36% for local abundance and geographical range size, and between 9 and 10% for habitat breadth. Main conclusions: The regional pool of woody plant species in Madidi exhibits phylogenetic signal in rarity that is consistent with biologically significant species‐level heritability.